KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA X SMAN 2 SINGINGI - Nurfika Ari Rianti; Dudung Burhanudin; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This study titled Essay Writing Ability Description Class X SMAN 2 Singingi . This study aims to determine what is the ability to write essay description of the class X SMAN 2 Singingi . The method used in this research is descriptive quantitative method . Data were students of Class X SMAN 2 Singingi that berjulah sample of 35 students . The results found in this study through three aspects: the accuracy of the title with the theme of high category with an average of 9.2 , the aspect of conformity content with the title essay category with the average being 8.4 and accuracy aspects of language use ( diction , sentence , paragraphs and punctuation ) being categorized with an average of 7.1 . Based on the calculation of average ability to write the essay description of the class X SMAN 2 Singingi category were namely 77.5.Keywords: accuracy aspect of the title with the theme of the article, suitability aspects content with the title essay , exactness aspects of language use ( diction , sentences , paragraphs and punctuation )